(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This study aimed to investigate the need for developing digital tools and open learning resources to support the acquisition of the 21st-century skills for faculty to achieve. Achieving this goal, a descriptive analytical methodology was used by administering a questionnaire to a purposive sample of 200 academic and faculty members at University of Bisha, located in the Aseer region of the Kingdom of Saudi Arabia (KSA). The results showed total agreement with an arithmetic mean of 3.61 and a standard deviation of 0.954 on the expected impact of developing digital tools and open learning resources on acquiring 21st-century skills. The study found full agreement on the expected relationship between the development of digital tools, open learning resources, and the acquisition of 21st-century skills, with an arithmetic mean of 3.59 and a standard deviation of 1.012. Regarding the challenges and difficulties that face developing digital tools and open learning resources, the results exposed full agreement with an arithmetic mean of 3.58 and a standard deviation of 0.977. Additionally, there was a correlation and effect for the years of experiences of the participants from their point of view regarding the challenges and difficulties of developing digital tools and open learning resources.